ESTETIKA ISLAM DALAM KONTEKS KEHIDUPAN SOSIAL - Setyo Widyawati (Greget, 2002)
The aim of this writing is to give commentary on Islamic Aesthetics In the frame of sicial life. The con.sequency of this is that islamic Aesthetics fixes two goals, worldly and heavenly goals. Moslems believe that heavenly goal is important than the worldly one, and to achieve this goal moslems need dzikrullah in any activity including working with arts. Dzikrullah means remembering A118h in an intense Consciousness with persistent intensity (istiqomah).Man needs art to express his feeling of beauty which is inherently born with him, while an expression of art becomes one of the manifestations of dzikruliah itself. Beauty is identified as art Islamic Aesthetics offers a concept of how to work with art in an Islamic way, and how to express beauty which contains truth and goodness. The supreme source of beauty is Allah Himself and He, too, the destination of beauty. The essence of art gets its reality in the brilliant brain of Allah. Consequently, artistic creativity generating from Allah’s beauty gives out spiritual values in broad spectrum.Islamic spirituality as an essence of islamic art has a close relation with the dimension of Islamic inner spirit, the dimension of inferiority of/slam. Al Quran and Al Hadits supply resources which inspire artists to get forms of Islamic inner dimension, the inspiration if which has the quality of supreme individual. Two examples of these forms are the calligraphy which is the art of writing Arabic characters and ten architecture of mosques.Calligraphy and the architecture of mosque are artistic works of supreme individual quality with the beauty reflected by Allah’s inspiration. Calligraphy reflects two kinds of beauties, the aesthetic and the trancendental ones. Islamic artistic objects show the values of beauty in themselves as far kinds of nd the trancendental ones. Islamic alues of beauty in themselves as faras generated from perpetual source of inspiration which will never stop flowing. Islamic spiritual message is the presence of consciousness of The One God through the beauty of artistic expressions formed by the artists.Keywords:Islamic art, dzikrullah, lslamic spirituality